The puzzle of industrial enterprises in Romania over a century: 1918-2017 - Luminita Chivu (Romanian Academy, National Institute for Economic Research, 2019)
The configuration of industrial enterprises in Romania, in terms of numbers and structure, in relation to their characteristics, mirrors the Romanian economy and society at large, in their chronological development. Marked by the changes in the technological and economic paradigm, by the legal-institutional framework and changes in the ownership regime, by the commercial policy guidelines on the background of the dominant economic doctrine, but also by the characteristics of the communities in which they were operating, in turn the 'architecture' of the industrial enterprises put a special footprint on the economic and social development. Our analyses are focusing on three major historical periods: a) the inter-war period, the arms industry, and the post-war reconstruction period of 1918-1947; b) the period of centralised economy (with nationalisation, collective farming, and planned economy as its corollary), 1948-1989; c) the period of transition to a market economy and the European Union integration, 1990-2017.
Keywords: D23; L11; L16; L22; L25; L52; N14; 330; industrialization; industrial restructuring; privatization; deindustrialization